KILLING OF THE ELDERLY: THE MACEDONIAN CUSTOM “SLAUGHTER OF THE OLD MEN” (Филологические заметки, 2024)
This paper addresses the problem of killing of elderly people, a custom commonly referred to as "slaughtering the elderly" in Macedonia. Examples of this myth are registered across various regions of Macedonia, including Ohrid, Bitola, Prilep, Veles, Skopje and the surrounding areas, Dojran, the surroundings of Kratovo, Negotino, Debar, Drimkol, and the expansive hilly-mountainous regions of Maleshevo and Mariovo. The motivations behind senicide were numerous. It was commonly thought that during times of famine, killing of the elderly was a means of conserving scarce food resources. In addition, senicide occurred as a result of land confiscation, where the property or cultivation rights of the elderly were transferred to their younger generations. In some cases, these killing were considered an act of mercy, especially when an individual suffered from an incurable disease, or faced the challenges of old age, when people could not meet even their most basic biological needs, thus becoming a burden to the family or the community. The traumatic experience of sons killing their fathers, according to traditions, led to the abandonment of this brutal custom.